Pengaruh Karakteristik Individu dan Kompetensi SDM Terhadap Prestasi Kerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kota Bima - Umratunisa Umratunisa; Firmansyah Kusumayadi; Muhammad Badar (Indo Publishing, 2026)
This study aims to examine the effect of individual characteristics and human resource (HR) competence on the job performance of employees at the Department of Population and Civil Registration of Bima City. This research employed an associative research design with a quantitative approach. The population consisted of 60 employees, while the sample comprised 43 civil servants selected using a purposive sampling technique. Data were collected through observation, questionnaires using a Likert scale, and literature review. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, t-test, and F-test with the assistance of SPSS version 22. The results of the study indicate that individual characteristics have a positive and significant effect on employees' job performance, with a t-value of 5.601 and a significance level of 0.000 < 0.05. Human resource competence also has a positive and significant effect on job performance, with a t-value of 5.991 and a significance level of 0.000 < 0.05. Simultaneously, individual characteristics and HR competence significantly affect employees' job performance, as indicated by an F-value of 71.218, which is greater than the F-table value of 2.911, with a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.781 indicates that 78.1% of the variation in employees' job performance is explained by individual characteristics and HR competence, while the remaining 21.9% is influenced by other variables not examined in this study. Based on the findings, it can be concluded that individual characteristics and human resource competence have a positive and significant effect, both partially and simultaneously, on the job performance of employees at the Department of Population and Civil Registration of Bima City. Therefore, improving individual characteristics and HR competence should be prioritized to enhance employees' job performance.